Children's exposure to second hand smoke at home: A cross-sectional study in Portugal. - Vitória, PD (2015)
Second-hand tobacco smoke (SHS) is a major indoor pollutant that causes serious health problems for all exposed, especially children. Children are often exposed to SHS at home, due to parental or other households' or guests' smoking. This study describes Portuguese children's exposure to SHS at home (total and by Portuguese main regions). In 2010/2011, a questionnaire was applied to a sample of Portuguese children in the 4th grade (N=3187, mean age 9.05±0.7 years, 51.1% male). Descriptive analysis, chi-square tests and crude odds ratios were performed. Of the participants, 62.9% of those with smoking parents and 19.2% of those with non-smoking parents were exposed to SHS at their home. Parental smoking varied significantly among regions and was significantly associated with children's exposure to SHS at home. Children's exposure to SHS at home was high, especially if their parents smoke. Children living in Lisbon Region presented the highest SHS exposure rate. The association of SHS exposure with geographic regions suggests the influence of social and contextual factors on smoking behaviour and on tobacco control effectiveness. Our findings highlight the need to effectively prevent children's SHS exposure at their home and to develop tailored tobacco control measures by region.